OPTIMALISASI PRODUKSI PERIKANAN BERKUALITAS BERBASIS DIGITAL YANG AMAN, DAN RAMAH LINGKUNGAN SEBAGAI PENINGKATAN EKONOMI MASYARAKAT PESISIR - Rifdah Dwinafiah; Siti Auliya Zahra Hasan (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Meeting public demand for high quality food is greatly influenced by good fisheries production. Quality fisheries production is influenced by the availability of fish food. In this context, the aquaculture sector has experienced significant growth and has great potential to meet the need for high quality fishery products throughout the world. However, investment is needed in developing local raw materials and reducing dependence on imports to overcome the problem of availability of fish feed raw materials, especially fish meal. In this effort, fish meal certification will ensure the quality of fish feed raw materials, which in turn improves the overall quality of fisheries production. In addition, the use of digital technology in the fisheries sector has played an important role in increasing production, ensuring environmental sustainability, and supporting the economy of coastal communities. However, the government, fisheries farmers and other related parties must work together to achieve the best results. The use of this technology is also driven by the development of digital infrastructure, education and training. Fisheries have great potential to become a sustainable economic force, maintain environmental sustainability, and provide great benefits to coastal communities and people around the world by combining high-quality fisheries production, development of local raw materials, and responsible application of digital technology. In conclusion, digitally based safe and environmentally friendly high-quality fisheries are an important step to achieve this goal.